Targeted metabolic profiling of methionine cycle metabolites and redox thiol pools in mammalian plasma, cells and urine - Behringer, Sidney; Wingert, Victoria; Oria, Victor; Schumann, Anke; Grünert, Sarah; Cieslar-Pobuda, Artur; Kölker, Stefan; Lederer, Ann-Kathrin; Jacobsen, Donald W.; Staerk, Judith; Schilling, Oliver; Spiekerkötter, Ute; et al. (Metabolites, 2019)
The concentration of thiol and thioether metabolites in plasma has diagnostic value in genetic diseases of B-vitamin metabolism linked to methionine utilization. Among these, cysteine/cystine (Cys/CSSC) and glutathione/oxidized glutathione (GSH/GSSG) act as cellular redox buffers. A new LC-MS/MS method was developed for the simultaneous detection of cystathionine (Cysta), methionine (Met), methionine sulfoxide (MSO), creatinine and the reduced and oxidized pairs of homocysteine (Hcy/HSSH), cysteine (Cys/CSSC) and glutathione (GSH/GSSG). A one-step thiol-blocking protocol with minimal sample preparation was established to determine redox thiol pairs in plasma and cells. The concentrations of diagnostic biomarkers Hcy, Met, Cysta, and Cys in a cohort of healthy adults (n = 53) agreed with reference ranges and published values. Metabolite concentrations were also validated in commercial samples of human, mouse, rat and Beagle dog plasma and by the use of a standardized ERNDIM quality control. Analysis of fibroblasts, endothelial and epithelial cells, human embryonic stem cells, and cancer cell lines showed cell specificity for both the speciation and concentration of thiol and thioether metabolites. This LC-MS/MS platform permits the fast and simultaneous quantification of 10 thiol and thioether metabolites and creatinine using 40 µL plasma, urine or culture medium, or 500,000 cells. The sample preparation protocols are directly transferable to automated metabolomic platforms.
Gesehen am 03.12.2019